Analysis economy base and non base and its development strategy in balikpapan city - Danna Solihin (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
This study aims to determine the change / shift in the economic structure in Balikpapan city, the determination of the base and non-base sector and its contribution to employment in the region. Data used in the form of secondary data time series 2 (two) periods, the first period (2004-2008) and the second period (2009-2013). It is analyzed by location quetiont (LQ), shift share, analysis of growth sectoral graphic, analysis ratio of labor and SWOT analysis. LQ analysis results indicate the period I and II, there were six (6) sector of the economy as sectors of a base in the city, such as manufacturing sector; electricity, gas and water supply; construction; trade, hotels and restaurants; transportation communication and financial sector, real estate and business services. Shift share analysis results indicate that the competitive sectors in the period I and II are electricity, gas and water supply and construction sectors. Labor Ratio analysis results show that in the period I and II, the sector that contributes the most in employment in the city is trade, hotel and restaurant sector. Furthermore, based on the results of SWOT analysis, strategy of regional development policy needs to be taken to optimize the utilization and management of its resources in improving the local economy and pursue economic structural shift towards a structure that is supported by economic sector based on renewable resources.